2009
DOI: 10.1021/ac900309z
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Colloidal Platinum Nanoparticles by MALDI-TOF Mass Spectrometry

Abstract: In this work, matrix assisted laser desorption ionization-time of flight (MALDI-TOF) mass spectrometry has been applied to characterize colloidal platinum nanoparticles synthesized in the 1 to 4 nm size range. These nanoparticles were prepared via a solution-based method in which the size could be tuned by varying reaction conditions, such as the alcohol used as a reductant. Poly(vinylpyrrolidone), or PVP, (MW = 29,000) was utilized as a capping agent to stabilize the synthesized particles in solution. A model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 36 publications
3
28
0
Order By: Relevance
“…The XPS binding energies revealed the presence of two peaks corresponding to the 3d 3/2 and 3d 5/2 transitions. In the case of prepared samples, the presence of Pd (II) on the surface of the Pd nanoparticles is attributed to the carbonyl function of the protecting polymer interacting with the metallic palladium, removing electron density from the surface, as has been established in our previous work [24] and by Somorjaiet al for Pt nanoparticles capped with this kind of agent [31][32][33]. In short, what appears in this case as Pd(II) in the XPS spectra, is attributed to the palladium atoms on the surface of the nanoparticle, which are electron deficient due to their interaction with the protecting polymer.…”
Section: Catalytic Performance For Naphthalene Oxidationmentioning
confidence: 56%
See 1 more Smart Citation
“…The XPS binding energies revealed the presence of two peaks corresponding to the 3d 3/2 and 3d 5/2 transitions. In the case of prepared samples, the presence of Pd (II) on the surface of the Pd nanoparticles is attributed to the carbonyl function of the protecting polymer interacting with the metallic palladium, removing electron density from the surface, as has been established in our previous work [24] and by Somorjaiet al for Pt nanoparticles capped with this kind of agent [31][32][33]. In short, what appears in this case as Pd(II) in the XPS spectra, is attributed to the palladium atoms on the surface of the nanoparticle, which are electron deficient due to their interaction with the protecting polymer.…”
Section: Catalytic Performance For Naphthalene Oxidationmentioning
confidence: 56%
“…In the case of metal oxide catalysts [7] such as CeO 2 or mixed oxides (CuZnO) full conversion is reached at temperatures between 250ºC and 270ºC, respectively. Whilst for the case of metals supported on different oxides such as Pt/SiO 2 [33] the optimum temperature for naphthalene oxidation was 250ºC. Shie et al [34] indicated that Pt/γ-alumina decreased the reaction temperature for 95% naphthalene total oxidation to 207ºC.…”
Section: Catalytic Performance For Naphthalene Oxidationmentioning
confidence: 99%
“…A model for determining the size of the metallic nanoparticle core from MALDI-TOF mass spectra is proposed here and results were successfully verified by the correlation with particle sizes figures obtained by transmission electron microscopy and X-ray diffraction [65].…”
Section: Matrix-assisted Laser Desorption/ionizationmentioning
confidence: 69%
“…In one of the first reports on NPs analysis by MALDI-MS, the technique was utilized to characterize platinum NPs, synthesized in the 1-4 nm size range, and capped with Poly(vinylpyrrolidone), PVP, in order to stabilize the PtNPs in solution [65]. A model for determining the size of the metallic nanoparticle core from MALDI-TOF mass spectra is proposed here and results were successfully verified by the correlation with particle sizes figures obtained by transmission electron microscopy and X-ray diffraction [65].…”
Section: Matrix-assisted Laser Desorption/ionizationmentioning
confidence: 99%
“…LDI can be applied to aerosol characterization by aerosol time-of-flight mass spectrometer (ATOF-MS), 13 providing valuable insights for functionalized NPs also by using time of flight (TOF) as detection system. 260,261 The LOD of element gold can be as low as 1 part per trillion (pg·mL -1 ).…”
Section: Mass Spectrometry (Ms)mentioning
confidence: 99%